Single Submission System (OSS) As A Feature to Simplify Business Licences (Case Study of the One-Stop Investment and Integrated Service Office (DPMPTSP) in Jepara Regency) - Frida Salma Ayumna; Riyan Andni; Iqbal Faza (Yayasan Adra Karima Hubbi, 2023)
Background. Licensing services for business actors or the public is one of the obligations that must be fulfilled by state administrators. Business actors and investors certainly really want fast and straightforward services and processes. The government as the licensing supervisor is the main legality for business actors. The function of licensing is to regulate activities that have the potential to cause disturbance to the public interest. The application procedure has strict policies but does not have to have a series of complicated processes. The government created a system in the form of Online Single Submission (OSS) to make it easier for business actors to manage business licences. The facilitator of the government in facilitating its implementation is assisted by the One-Stop Investment and Integrated Service Office. Purpose. The purpose of this research is to find out how the performance of the Investment Service and One Stop Integrated Services is and also to find out what obstacles occur in the field and how solutions are produced to solve various existing obstacles. Method. The research method in this study is to use qualitative methods and data collection methods using interview techniques to find out information from respondents. Results. The results of the discussion of this study indicate that the Investment and One-Stop Service Office has provided good and responsive service so that existing constraints can be resolved immediately. Conclusion. The Online Single Submission (OSS) system is implemented to accelerate business licensing at the Jepara Regency Investment and One-Stop Integrated Service Office (DPMPTSP) as a public service facility under the Jepara Regency Investment and One-Stop Integrated Service Office (DPMPTSP). To obtain a commercial or operational business licence, it must start with registration through the OSS website.